El control interno y su relación con la producción de la agrícola bananera soledad cantón La Mana, provincia de Cotopaxi, año 2012 - Albarracín Campaña, Diana Carolina (2013)
The research was to determine the internal control and its relationship to the production of agricultural Banana SOLEDAD , during 2012 , in order to increase efficiency through the recommendations of an audit. General characteristics of Agricultural Banana SOLEDAD was investigated in the first instance. After a definition of the basic terms used for this planning was done , once identified these concepts proceeded to run the assessment of internal control . In the previous visit to the company , was to determine which weaknesses were found in departments and defining critical areas with emphasis on internal controls. Internal Control for the purpose of measuring efficiency in compliance with policies and procedures in order to establish corrective results were evaluated. A small survey was carried out to reviewers to detect deficiencies which affect productivity are resulting contracts staff are doing any of 1-3 months. He then proceeded to apply the questions of internal control questionnaires and this helped discover the most common risks and verified that there were three risks that were affecting the growth of production in the company. It was able to detect that there are deficiencies in the control environment , there are also risks that hinder the growth of the company, could also be noted that the control activities manages its policies and procedures to convenience, do not use the administrative tools properly, and monitoring activity is not changed periodically. Once the papers of risk findings conducted proceeded to make their narratives and interpretations respetivas recommendations . That is why I believe that this research will be useful in the search for solutions to improve productivity and contribute to the development and growth of the company.